Universal, not Particular: A Study of metà gynaikós in John 4,27 - Ashe, Materou (Biblica, 2024)
Μετὰ γυναικός in John 4,27 is anarthrous and from the perspective of grammar it could be translated either as 'with a woman' or 'with the woman'. This paper critically evaluates both translations of μετὰ γυναικός in John 4,27 mainly following grammatical philological analysis. This study proposes the first extended argument for the interpretation of μετὰ γυναικός in John 4,27 as a universal statement about women instead of a particular reference to a Samaritan woman. Based on an analysis of the literary context this study argues that John 4,1-42 lays special emphasis on the womanhood of the woman in various ways and that μετὰ γυναικός should be interpreted and translated as 'with a woman'.